Palladium nanoparticles supported on chitin-based nanomaterials as heterogeneous catalysts for the Heck coupling reaction - Jin, Tony; Hicks, Malickah; Kurdyla, Davis; Hrapovic, Sabahudin; Lam, Edmond; Moores, Audrey (Beilstein Journal of Organic Chemistry, 2020)
In this report, chitin and chitosan nanocrystals were used as biomass-based supports for Pd nanoparticles (NPs) used as a heterogeneous catalyst for the Heck coupling reaction. By using a one-pot fabrication method, a Pd salt precursor was directly reduced and deposited onto these nanocrystal catalysts. Characterization of these nanocomposites showed disperse Pd NPs on the surfaces of the chitinous nanocrystals. Heck coupling model reactions revealed full product yield in relatively benign conditions, outcompeting the use of other catalysts supported on biomass-based nanomaterials, including cellulose nanocrystals. These initial results show the potential for using chitinous nanomaterials as effective catalyst supports in cross-coupling reactions.
Keywords: chitin; chitosan; Heck coupling; heterogeneous catalysis; nanomaterial

(untitled) - Thomas, B.; Raj, M. C.; B, A. K.; H, R. M.; Joy, J.; Moores, A.; Drisko, G. L.; Sanchez, C. (Chem. Rev., 2018)

(untitled) - Dufresne, A. (Mater. Today, 2013)

(untitled) - Seabra, A. B.; Bernardes, J. S.; Fávaro, W. J.; Paula, A. J.; Durán, N. (Carbohydr. Polym., 2018)

(untitled) - Chowdhury, R. A.; Nuruddin, M.; Clarkson, C.; Montes, F.; Howarter, J.; Youngblood, J. P. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Wang, N.; Ouyang, X.-K.; Yang, L.-Y.; Omer, A. M. (ACS Sustainable Chem. Eng., 2017)

(untitled) - Kaushik, M.; Moores, A. (Green Chem., 2016)

(untitled) - Cirtiu, C. M.; Dunlop-Brière, A. F.; Moores, A. (Green Chem., 2011)

(untitled) - Lam, E.; Hrapovic, S.; Majid, E.; Chong, J. H.; Luong, J. H. T. (Nanoscale, 2012)

(untitled) - Seyednejhad, S.; Khalilzadeh, M. A.; Zareyee, D.; Sadeghifar, H.; Venditti, R. (Cellulose, 2019)

(untitled) - Kaushik, M.; Basu, K.; Benoit, C.; Cirtiu, C. M.; Vali, H.; Moores, A. (J. Am. Chem. Soc., 2015)

(untitled) - Serizawa, T.; Sawada, T.; Wada, M. (Chem. Commun., 2013)

(untitled) - Chen, X.; Yang, H.; Yan, N. (Chem. – Eur. J., 2016)

(untitled) - MacLeod, J. A.; Kuo, S.; Gallant, T. L.; Grimmett, M. (Can. J. Soil Sci., 2006)

(untitled) - Marchessault, R. H.; Morehead, F. F.; Walter, N. M. (Nature, 1959)

(untitled) - Zeng, J.-B.; He, Y.-S.; Li, S.-L.; Wang, Y.-Z. (Biomacromolecules, 2012)

(untitled) - Jin, T.; Kurdyla, D.; Hrapovic, S.; Leung, A. C. W.; Régnier, S.; Liu, Y.; Moores, A.; Lam, E. (Biomacromolecules, 2020)

(untitled) - Shigemasa, Y.; Matsuura, H.; Sashiwa, H.; Saimoto, H. (Int. J. Biol. Macromol., 1996)

(untitled) - Khor, E.; Lim, L. Y. (Biomaterials, 2003)

(untitled) - Kaushik, M.; Chen, W. C.; van de Ven, T. G. M.; Moores, A. (Nord. Pulp Pap. Res. J., 2014)

(untitled) - Kaushik, M.; Li, A. Y.; Hudson, R.; Masnadi, M.; Li, C.-J.; Moores, A. (Green Chem., 2016)

Stilbenes: applications in chemistry, life sciences and materials science - Likhtenshtein, G. (Wiley-VCH, 2009)

(untitled) - Henriksen, S. T.; Norrby, P.-O.; Kaukoranta, P.; Andersson, P. G. (J. Am. Chem. Soc., 2008)

(untitled) - Jadhav, S.; Kumbhar, A.; Salunkhe, R. (Appl. Organomet. Chem., 2015)

(untitled) - Kamal, A.; Srinivasulu, V.; Seshadri, B. N.; Markandeya, N.; Alarifi, A.; Shankaraiah, N. (Green Chem., 2012)

(untitled) - Premi, C.; Jain, N. (RSC Adv., 2016)

(untitled) - Pei, X.; Li, Y.; Deng, Y.; Lu, L.; Li, W.; Shi, R.; Lei, A.; Zhang, L. (Carbohydr. Polym., 2021)